The hydrogen economy : opportunities, costs, barriers, and R & D needs (National Academies Press, 2004)
The announcement of a hydrogen fuel initiative in the President's 2003 State of the Union speech substantially increased interest in the potential for hydrogen to play a major role in the nation's long-term energy future. Prior to that event, DOE asked the National Research Council to examine key technical issues about the hydrogen economy to assist in the development of its hydrogen R & D program. Included in the assessment were the current state of technology; future cost estimates; CO2 emissions; distribution, storage, and end use considerations; and the DOE RD & D program. The report provides an assessment of hydrogen as a fuel in the nation's future energy economy and describes a number of important challenges that must be overcome if it is to make a major energy contribution. Topics covered include the hydrogen end-use technologies, transportation, hydrogen production technologies, and transition issues for hydrogen in vehicles.